First validation of the G-8 geriatric screening tool in older patients with glioblastoma. Issue 1 (January 2019) - Deluche, Elise; Leobon, Sophie; Lamarche, Francois; Tubiana-Mathieu, Nicole
Abstract: Introduction: Management of glioblastoma, with a very poor prognosis, remains a challenge in older patients because of coexisting comorbidities and the increased risk of toxic treatment effects. The use of screening tools to identify vulnerable patients is essential. This study was performed to establish whether the G8 scale can be used for screening older patients with glioblastoma. Methods: We retrospectively reviewed the files of patients assessed by the G8 scale and diagnosed with glioblastoma at a single center from January 2010 to July 2017. Patients aged 65 years or older were classified into three groups (more efficiently than two groups) according to their G8 score to identify those with a poor prognosis: high score group, G8 score 14.5–17; intermediate score group, G8 score 10.5–14; and low score group, G8 score < 10.5. Results: Of 89 patients, 19% were classified into the high score group, 43% into the intermediate score group, and 38% into the low score group. Median overall survival was four months in the low score group, 15 months in the intermediate score group, and 42 months in the high score group ( p  < .0001). On multivariate analysis, G8 score was a significant independent predictor of overall survival (hazard ratio: 55.46; 99.5% confidence interval: 13.42–229.13; p  < .0001). Conclusions: Here, we highlighted the possibility of using the G8 score, with possibly three cut-offs, in the management of older patients with glioblastoma and determined the prognostic role of this quick and easy screening tool.